Cronus e kairós: reflexões sobre temporalidade laboral e solvência social - Sabóia, Iratan Bezerra de (2007)
In this paper, we analyzed the time as a privilege category of subject and society study; aiming to analyze its action as a social solvent when presents itself in the new configurations between time and work in contemporaneity, we performed a theoretical analysis of time category and its new ways of presenting itself in work contemporaneity. Thereunto, we delimitated a few study fields where temporality inserted itself as category, as of Philosophy, Physics, Biology and Sociology, we studied the work Time, the free Time and the leisure Time. Based on these studies, we delimitated a few Psychology study fields of temporality, so we can finally focus in the temporality issue for Psychoanalysis. Once the subjective temporality was delimitated, we could search for the interface between it and the world, finding a temporality marked by social mediation. In this context, we verified the time acting with the work, forming one of the categories which works as social glue. Analyzing the new configurations admitted by the labor temporality, after the work has become predominant social category, we verified that it can lose its society wide glue characteristic and present itself as a social solvent in a few social groups, fortifying other groups’ attachments, helping, thereby, in time ghettos formation related to work.